Investigating Gross Motor Skills in Children Aged 5-6 Years at Islamic-Based Kindergartens - Azzahra, Vira; Kartika, Wilda Isna; Maghfirah, Febry (Faculty of Education and Teacher Training of UINSI Samarinda, 2024)
Gross motor skills in children aged 5 to 6 support their physical progress and overall abilities. In this age range, children are in an essential phase of improving muscle strength, body coordination, and other motor skills, which can be acquired through a variety of physical activities, both structured and free. This study evaluates gross motor development in children aged 5 to 6 years enrolled in kindergartens in the Sungai Kunjang sub-district, Samarinda. The research method used was a quantitative approach with a survey design, and data analysis was conducted using SPSS software version 22.0. The population in this study was 13 kindergartens in the Sungai Kunjang Subdistrict of Samarinda. The samples in this study were two kindergartens, which were determined based on the specified criteria (purposive sampling): the kindergarten located in Sungai Kunjang Subdistrict, an Islamic-based kindergarten using the Merdeka Curriculum. Data were collected by distributing questionnaires to teachers in two kindergartens in Sungai Kunjang Subdistrict, Samarinda City. The findings showed that the children's gross motor skills were still relatively low, with the questionnaire indicating that of the 17 indicators observed, most of the children's skills were in the Beginning to Develop (MB) category, with an average score of 1.33. These results imply that further stimulation, such as educational game tools, should support children's gross motor development in kindergartens in Sungai Kunjang District, Samarinda.